Effects of 30% dried distillers grains with solubles and 5% added fat prior to slaughter on growth performance, carcass characteristics, and economics of finishing pigs - Coble, Kyle F.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Two groups of pigs (n = 1,258, initially 233.2 lb; group 1 PIC 337 × 1050; group 2 PIC 327 × 1050) were used in a 20-d experiment to determine the effects of 30% dried distillers grains with solubles (DDGS) and 5% added fat prior to slaughter on growth performance, carcass characteristics, and economics of finishing pigs. There were a total of 20 replications per treatment. All pigs were fed a common diet with 30% DDGS until 20 d prior to slaughter, at which point they were weighed and allotted to dietary treatments. The dietary treatments were arranged in a 2 × 2 factorial with 2 diet types, a corn-soybean meal–based diet with or without 30% DDGS and added fat of 0 or 5% (group 1 = tallow; group 2 = choice white grease). Diets were formulated on a standardized ileal digestible (SID) lysine basis and balanced on an SID lysine to NE ratio. There were no treatment × group interactions for any of the measured responses, so data for the two groups were combined for analysis. For the overall experiment, there was a tendency (P < 0.10) for a diet type × added fat interaction for ADG; this interaction was significant (P < 0.05) for F/G and caloric efficiency on an ME and NE basis. These were the result of pigs fed the diet with 30% DDGS having greater ADG and F/G improvements when fat was included compared with those fed the corn-soybean meal–based diet without DDGS. For the caloric efficiency interaction, pigs fed 30% DDGS had an improvement with added fat, whereas those fed the corn-soybean meal–based diet with added fat had worse caloric efficiency than pigs fed the corn-soy diet without added fat. Although diet type did not affect final live weight, pigs fed the diet containing DDGS had reduced HCW (P < 0.05), which was the result of reduced carcass yield (P < 0.05). Adding 5% fat to the diet containing DDGS did not improve carcass yield. Jowl fat iodine value was increased by added fat (P < 0.05) and feeding DDGS (P < 0.05). For economics, there was a diet type × added fat interaction (P < 0.05) for cost per pound of gain, which was the result of a larger increase in cost for pigs fed added fat in the corn-soybean meal–based diet compared with the diet containing DDGS. Income over feed cost did not differ among dietary treatments. In conclusion, adding 5% fat to finishing pig diets containing 30% DDGS approximately 20 d prior to slaughter improved ADG and F/G but did not overcome the reduction in carcass yield from feeding DDGS.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Finishing pig; Fiber; Fat; Yield